Effects of Gramma Radiation on Azuki Bean Weevil, Callosobruchus chinensis (L.) - Jakarpong Supawan; Praparat Hormchan; Manon Sutantawong; Arunee Wongpiyasatid (Agriculture and Natural Resources, 2005)
Effects of gamma radiation at various doses on eggs, larvae, pupae and adults of azuki bean weevil, Callosobruchus chinensis (L.) were studied. It was found that there were no significant differences between percent egg mortalities at 40 and 80 Gy and among 120, 160 and 180 Gy. As for the larvae, percent mortalities at all doses were significantly different from that of the control. Significant differences were also found among tested doses from that of the control in percent pupal mortality. After 4 and 7 days of irradiation, percent adult mortalities were found to be significantly different from those of the control at every dose. No significant differences were found among percent mortalities at all tested doses between 4 and 7 days. Percent sterilities at 100 and 120 Gy were not significantly different. When untreated male mating with treated female, there were significant differences in fecundity from the control and from among one another. In treated larvae at 100, 300 and 500 Gy, of all doses the degrees of melanization decreased with the increasing dose. The percent phenoloxidase (PO) activities of the treated larvae reduced compared with that of the control.